2008
DOI: 10.1007/s12020-008-9115-5
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and diabetes mellitus

Abstract: Better understanding of the physiological role of the vitamin-D system, in particular its potential effects on inflammatory and autoimmune conditions as well as on insulin secretion and possibly also on insulin resistance, increased the interest in its potential role in prevention and control of the diabetic condition, both type-1 and -2 diabetes. Both these conditions are associated with inflammation and type-1 diabetes also with an autoimmune pathology. Indeed, animal and human studies support the notion tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
113
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(124 citation statements)
references
References 127 publications
(167 reference statements)
4
113
0
7
Order By: Relevance
“…It seems to suppress the antigen capacity of macrophages, inhibit the matu ration of dendritic cells, modulate the development of CD4 lymphocytes and inhibit the production of cyto kines such as interferon (IFN) and interleukin2 (IL2). These cytokines are known for activate macrophages and cytotoxic T cells, that lead to the destruction of pancreatic cells (143).…”
Section: B) Vitamin D and Diabetesmentioning
confidence: 99%
“…It seems to suppress the antigen capacity of macrophages, inhibit the matu ration of dendritic cells, modulate the development of CD4 lymphocytes and inhibit the production of cyto kines such as interferon (IFN) and interleukin2 (IL2). These cytokines are known for activate macrophages and cytotoxic T cells, that lead to the destruction of pancreatic cells (143).…”
Section: B) Vitamin D and Diabetesmentioning
confidence: 99%
“…Apart from this, accumulating evidence exists that vitamin D deficiency indirectly contributes to the development of arterial hypertension, diabetes mellitus, dyslipidemia, and other cardiovascular risk factors [51][52][53]. It was also shown that vitamin D exerts direct anti-atherosclerotic effects on endothelial and vascular smooth muscle cells [3,4,51].…”
Section: Indirect Effects Of Vitamin D On the Myocardiummentioning
confidence: 99%
“…Vitamin D status influences insulin secretion/insulin sensitivity. The effect of vitamin D on insulin secretion may be mediated by changes in intracellular calcium concentration in beta cells [21,22].Vitamin D improves insulin sensitivity by its anti-inflammatory activity. Vitamin D attenuates the expression of proinflammatory cytokines involved in insulin resistance (IR) such as interleukins, IL-1, IL-6, TNF-a, also down regulates NF-Kb (Nuclear factor) activity [23,24].…”
Section: Introductionmentioning
confidence: 99%